Synthesis and electrical characterization of Nd-Doped BaTiO3 for anti-resonance piezoelectric device - Tuan Amirah Tuan Sulong (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2017)
The objectives of this study are ; to synthesize and analyse the physical, structural, electrical and piezoelectric properties of Nd-doped BaTiO3 (Ba1-xNdxTiO3) in the range of (0<x<0.13) ; to determine the phase transition by doping Nd into BaTiO3 ; to determine the composition which exhibit highest permittivity, piezoelectric charge constant, piezoelectric voltage constanst and lowest dielectric loss among Nd-doped BaTiO3 compositions at room temperature.